Online Consumer Satisfaction During COVID-19: Perspective of a Developing Country - Rao, Yonghui; Saleem, Aysha; Saeed, Wizra; Ul Haq, Junaid (Frontiers in Psychology, 2021)
A conceptual model based on the antecedents and consequences of online consumer satisfaction has been proposed and empirically proved in this study. Data were collected during Smart Lockdown of COVID-19 from eight hundred respondents to observe the difference between perceived and actual; and direct and indirect e-stores. Confirmatory factor analysis was used to observe the validity of the data set. The structural equation modeling technique was used to test the hypotheses. The findings indicated that consumers feel more satisfied when they shop through direct e-store than indirect e-store, whereas their perception and actual experience is different. Implications have also been added to the study.